Analysis of Availability and Size Distribution of Giant Shrimp (Macrobranchium sp) in River Togafo, Ternate City, North Mollucas Province - Abubakar, Yuyun; Sunarti, Sunarti; Salim, Fajria Dewi; Rina, Rina; Abubakar, Salim; Serosero, Rugaya; Fadel, Ariyati H (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Giant prawns (Macrobrachium sp) are one of the freshwater aquaculture commodities that have high economic value (Murtidjo, 1992). The demand for giant prawns in Indonesia has only been met by 40% of all existing demand (Tambunan, 2009. The aim of the research was to analyze the abundance of giant prawns and the size distribution of giant prawns in Togafo Village, West Ternate District, Ternate City. The purposive sampling method was used in this research. Then the sampling points that had been determined using purposive sampling were marked with coordinates with the help of the Global Positioning System (GPS). For the research location, it was divided into 3 observation stations. First, the shrimp body length and weight were measured using calipers and analytical scales. Abundance relative = individual/trip and Distribution of length measurements and distribution of shrimp weight measurements can be grouped using the equation (Effendie, 1979) as follows: K = 1 + 3.3 log n. Note: K = Number of Interval Classes, n = Number of Observation Data, log = Logarithm. Based on the results, the highest abundance of giant prawns (Macrobrachium sp) is at station 3 with a value of 0.575 ind., station 1 is 0.336, the lowest is at station 2 with a value of 0.088 ind. Size Distribution The smallest ranges between 40.17-52.19 mm and the largest ranges between 105.25 – 117.27 mm.